1995
DOI: 10.1149/1.2050008
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxide Growth on Tantalum with AC + DC Fields: I . Experimental Procedures and Results

Abstract: The small signal ac response of the ionic conductivity growth process was described using the ionic admittivity defined as the (complex) ratio of the ac components of ionic current density and field since, unlike the ratio of current and voltage (admittance), this gives results independent of film thickness. Ideally constant ac and dc components of field were approximated by applying a ramp plus an ac voltage increasing with the average film thickness. Growth due to the ac ionic current produces an out of phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…This similar-shaped EIS spectrum was early measured by De Wit et al for anodized Al, Kelly for passivated Ti, and Keddam and co-workers , for passivated Fe. And now, it is so common for (and only limited to) the valve metals that it has been observed on most valve metals, such as Ti, , W, Nb, ,,, Mo, ,, Al, , Fe, ,, Ta, , and Bi …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This similar-shaped EIS spectrum was early measured by De Wit et al for anodized Al, Kelly for passivated Ti, and Keddam and co-workers , for passivated Fe. And now, it is so common for (and only limited to) the valve metals that it has been observed on most valve metals, such as Ti, , W, Nb, ,,, Mo, ,, Al, , Fe, ,, Ta, , and Bi …”
Section: Introductionmentioning
confidence: 99%
“…This type of EIS spectra is featured by a high-frequency capacitive loop, a middle-frequency inductive loop, and a low-frequency vertical capacitive line (Figure a), and it can be modeled by the equivalent electrical circuit shown in Figure b. ,,,, A typical method widely used for analyzing and interpreting this type of EIS spectra is the surface-charge approach (SCA), ,,, which is developed and updated by Bojinov and co-workers based on the point-defect model (PDM) of Macdonald and co-workers, the ideas of De Wit et al and Young and co-workers, , and the equivalent electrical circuit model shown in Figure b. With SCA, the EIS behaviors relating to the film formation−dissolution have been investigated for anodized Ti, W, , Nb, , Mo, , Bi, Ta, Al, and Fe …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that in situ EIS has been widely applied to study the growth of barrier-type oxide films on the surface of valve metals. [28][29][30] Unfortunately, the collected data cannot be directly used for description the processes occurring during porous AAO formation because they are much more complex. Here EIS is applied for in situ study of the thickness of the barrier layer during the porous AAO films grown on high-purity aluminium.…”
mentioning
confidence: 99%